Multifunctional nano-loaded porous micro-aggregate as well as preparation method and application thereof
By using multi -functional nano -loaded porous microcomposions in building materials, combined with modified carbonate particles and nano -function materials, the problem of insufficient conductivity and mechanical performance of traditional concrete materials has been solved, and the development of high -performance building materials is achieved.
Patent Information
- Application Number
- CN202411373599.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Traditional concrete materials have insufficient electrical conductivity and mechanical properties, making it difficult to meet the demand for high-performance materials in modern buildings.
The multi -function nano -loaded porous microcomputer is used to improve the conductivity and mechanical properties of building materials through the combination of modified carbonate particles and nano -function materials. After the material is rough and porous by the surface of the carbonate substrate, the material loads nano -function materials by impregnating and thermal treatment technology.
The conductivity and mechanical properties of architectural materials have been achieved significantly improved. It is suitable for large -scale production, low cost, and suitable for various construction areas.
Smart Images

Figure CN119330622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a multifunctional nano-loaded porous micro-aggregate and a preparation method and application thereof. Background Art
[0002] Concrete is one of the most widely used building materials in the world, but the performance of traditional concrete limits its potential in different application areas. One of the key components of concrete is aggregate, including fine aggregate and coarse aggregate, which occupies more than 60% of the volume of concrete. Common sand and gravel aggregates and machine-made sand usually have a dense structure and smooth surface, which limits the versatility of concrete. Aggregates play a key role in concrete, but their functions are single, including providing mechanical support and filling, and they are also weak areas where concrete performance deteriorates. In order to meet the diverse demands of modern society for the performance of concrete materials, a new type of material and preparation method are urgently needed to achieve the functional transformation of concrete.
[0003] At the same time, the commonly used nano-loaded porous materials at this stage, such as molecular sieves and MOF (metal organic framework) nanomaterials, perform well in terms of loading effects, but their synthesis scale is usually limited and it is difficult to meet the large-scale utilization needs of building materials such as concrete. Their synthesis process is complex and costly, and they cannot effectively meet the requirements of large-scale construction projects for conductivity and strength.
[0004] Therefore, it is necessary to provide a nano-loaded porous material with good electrical conductivity and mechanical properties. Summary of the invention
[0005] In view of this, the present application provides a multifunctional nano-loaded porous micro-aggregate and a preparation method and application thereof, which are used to solve the problem of how to improve the electrical conductivity and mechanical properties of building materials.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a multifunctional nano-loaded porous micro-aggregate, including modified carbonate particles and nano-functional materials loaded on the modified carbonate particles; the modified carbonate particles are obtained by roughening and / or making porous carbonate matrix materials.
[0007] Preferably, the carbonate matrix material comprises limestone and / or dolomite.
[0008] Preferably, the nano-functional material includes one or more of graphene, carbon nanotubes, and silver nanoparticles.
[0009] Preferably, the particle size of the nano-functional material is 10-20 nm.
[0010] Preferably, the particle size of the carbonate matrix material is 20-50 μm.
[0011] In a second aspect, the present application provides a method for preparing a multifunctional nano-loaded porous micro-aggregate, comprising the following steps: S1. calcining the carbonate matrix material to obtain modified carbonate particles; S2. Using an impregnation method, the nano-functional material is loaded on the modified carbonate particles to obtain a porous micro-aggregate precursor; S3. Heat-treating the porous micro-aggregate precursor to obtain multifunctional nano-loaded porous micro-aggregates.
[0012] Preferably, in step S1, the calcination temperature is 600-900°C, and the calcination time is 2-4h.
[0013] Preferably, in step S2, the mass ratio of the nano-functional material to the carbonate matrix material is 5-8:100.
[0014] Preferably, in step S3, the heat treatment temperature is 100-200° C., and the heat treatment time is 1-3 h.
[0015] In a third aspect, the present application provides an application of a multifunctional nano-loaded porous micro-aggregate in building materials.
[0016] The beneficial effects of the present application are as follows: the present application uses carbonate materials from a wide range of sources through low-energy rapid calcination technology to make the surface of the carbonate material porous / roughened, which is beneficial to the loading of nano-functional materials, and then through heat treatment, the loading degree of the nano-functional materials and modified carbonate materials is further enhanced. This solution is suitable for large-scale production, low cost, and the resulting material has good conductivity and mechanical properties, and is suitable for various construction fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is an electron microscope image of the modified carbonate particles obtained in Example 1; Figure 2 This is an electron microscope image of the modified carbonate particles obtained in Example 2; Figure 3 The compressive strength test results of different materials; Figure 4 The resistivity test results of different materials. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] In a first aspect, the present application provides a multifunctional nano-loaded porous micro-aggregate, including modified carbonate particles and nano-functional materials loaded on the modified carbonate particles; the modified carbonate particles are obtained by roughening and / or making porous carbonate matrix materials.
[0020] In the present application, most (50-90%) of the nano-functional materials are loaded on the surface of the modified carbonate particles, and a small part (1-50%) is loaded inside the modified carbonate particles.
[0021] In some embodiments, the carbonate matrix material includes limestone and / or dolomite.
[0022] In some embodiments, the nano-functional material includes one or more of graphene, carbon nanotubes, and silver nanoparticles.
[0023] In some embodiments, the particle size of the nano-functional material is 10-20 nm.
[0024] In some embodiments, the particle size of the carbonate matrix material is 20-50 μm.
[0025] The present application provides a method for preparing a multifunctional nano-loaded porous micro-aggregate, comprising the following steps: S1. calcining the carbonate matrix material to obtain modified carbonate particles; S2. Using an impregnation method, the nano-functional material is loaded on the modified carbonate particles to obtain a porous micro-aggregate precursor; S3. Heat-treating the porous micro-aggregate precursor to obtain multifunctional nano-loaded porous micro-aggregates.
[0026] In the present application, step S1 uses widely available carbonate materials as matrix materials. These materials have a natural porous structure with a porosity of 30-90%, which is convenient for subsequent functional transformation. After low-temperature calcination, the surface of the carbonate matrix material forms a porous or rough shape, while the interior is still a carbonate material; steps S2 and S3 load the nanofunctional material into the interior and / or surface of the modified carbonate particles through a process of impregnation mixing and then heat treatment. This process involves immersing the carbonate material in a solution containing the nanofunctional material, followed by heat treatment to ensure uniform distribution and good adhesion of the nanomaterial.
[0027] This application uses bulk carbonate materials as a matrix and a low-energy fast-burning preparation method to achieve large-scale application of porous materials; traditional building materials have limited functionality and cannot meet a variety of application requirements. This application loads nanomaterials and leaves most of the nanofunctional materials on the surface of the matrix, so that the building materials have certain functional properties, such as conductivity, adsorption, and flame retardancy. These properties expand the application areas of concrete, such as smart sensing, electromagnetic shielding, and pollutant control.
[0028] In some embodiments, in step S1, the calcination temperature is 600-900°C, the calcination time is 2-4 hours, and step S1 also includes washing and drying the carbonate matrix material to remove surface impurities.
[0029] In some embodiments, in step S2, the mass ratio of the nano-functional material to the carbonate matrix material is 5-8:100. The process of the impregnation method is: immersing the modified carbonate particles in the dispersion of the nano-functional material to ensure full contact and adsorption. In this process, if there is too much nano-functional material, the subsequent heat treatment will be affected, so that the nano-functional material will precipitate and cannot be well attached to the surface of the modified carbonate particles. If there is too little nano-functional material, the dispersion will be uneven.
[0030] In some embodiments, in step S3, the heat treatment temperature is 100-200° C., and the heat treatment time is 1-3 hours.
[0031] Within this limited range, it is beneficial for the nano-functional materials to be fixed inside and / or on the surface of the modified carbonate particles. If the temperature is too low, the water cannot be evaporated quickly, and it is not easy for the nano-functional materials to remain on the surface, while if the temperature is too high, the size of the nano-functional materials will be affected.
[0032] The present application provides an application of a multifunctional nano-loaded porous micro-aggregate in building materials, in particular, as conductive concrete and / or flame-retardant concrete.
[0033] This application uses bulk carbonate materials as matrix materials, and the sources of materials are wide. Conductive concrete is prepared by loading conductive materials such as nano-graphene, carbon nanotubes and other nano-functional materials to achieve functional transformation of conventional carbonate aggregates. This aggregate not only maintains the basic structural role of aggregates in concrete, but also introduces additional functionality, which can be used in geothermal systems, smart buildings, electromagnetic shielding and other fields, and provides broad prospects for the functionalization of concrete materials to meet the needs of different applications and functionalization.
[0034] The present solution is further described below through specific embodiments.
[0035] Example 1 A method for preparing multifunctional nano-loaded porous micro-aggregates comprises the following steps: S1. Limestone ore with a particle size of 30 µm was calcined at 600 °C for 2 h to obtain modified carbonate particles with porous surfaces. The electron microscopy results are as follows: Figure 1 As shown, its surface is porous calcium oxide; S2. The modified carbonate particles are mixed with ethanol to obtain a suspension, and graphene nanosheets with a particle size of 10 nm are added to the suspension. After ultrasonic dispersion, a porous micro-aggregate precursor is obtained, wherein the mass of the graphene nanosheets is 8% of the mass of the limestone; S3. The porous micro-aggregate precursor is heated at 105°C for 2 h and dried to allow the graphene nanosheets to be firmly loaded on the modified carbonate particles, thereby obtaining a multifunctional nano-loaded porous micro-aggregate.
[0036] Example 2 A method for preparing multifunctional nano-loaded porous micro-aggregates comprises the following steps: S1. Dolomite with a particle size of 50 µm was calcined at 700 °C for 1 h to form rough magnesium oxide on the surface, thus obtaining modified carbonate particles. The electron microscopy results are as follows: Figure 2 As shown, its surface is rough magnesium oxide; S2. The modified carbonate particles are mixed with ethanol at a solid-liquid ratio of 16:100 to obtain a suspension, carbon nanotubes with a particle size of 10 nm are added to the suspension, and after ultrasonic dispersion, a porous micro-aggregate precursor is obtained, wherein the mass of the carbon nanotubes is 5% of the mass of the limestone; S3. The porous micro-aggregate precursor is heated at 105°C for 2 h and dried to allow the graphene nanosheets to be firmly loaded on the modified carbonate particles, thereby obtaining a multifunctional nano-loaded porous micro-aggregate.
[0037] Example 3 A method for preparing multifunctional nano-loaded porous micro-aggregates comprises the following steps: S1. The limestone ore with a particle size of 40 µm was calcined at 650°C for 2 h, and then rapidly heated to 900°C and maintained for 5 minutes to obtain modified carbonate particles with porous surfaces; S2. Silver nanoparticles with an average diameter of 10-20 nm are dispersed in deionized water containing a surfactant, and then mixed with modified carbonate particles, and after ultrasonic stirring, a porous micro-aggregate precursor is obtained; S3. The porous micro-aggregate precursor is heated at 200°C for 1 hour and dried to obtain a multifunctional nano-loaded porous micro-aggregate.
[0038] Example 4 A method for preparing a multifunctional nano-loaded porous micro-aggregate, the other contents of which are the same as those of Example 1, except that the graphene nanosheets are replaced by carbon nanotubes.
[0039] Example 5 A method for preparing a multifunctional nano-loaded porous micro-aggregate, the other contents of which are the same as those of Example 2, except that the carbon nanotubes are replaced by graphene nanosheets.
[0040] Comparative Example 1 A method for preparing multifunctional nano-loaded porous micro-aggregate, the other contents of which are the same as those of Example 1, except that steps S2 and S3 are not included, so that porous calcium oxide is obtained.
[0041] Comparative Example 2 A method for preparing multifunctional nano-loaded porous micro-aggregate, the other contents of which are the same as those of Example 2, except that steps S2 and S3 are not included, and rough magnesium oxide is obtained.
[0042] Test and Evaluation The multifunctional nano-loaded porous micro-aggregates obtained in Examples 1, 4 and Comparative Example 1 were used as aggregates to prepare mortars, and the multifunctional nano-loaded porous micro-aggregates obtained in Examples 2, 5 and Comparative Example 2 were used as aggregates to prepare mortars. After the mortars were cured, their compressive strength and resistivity of the test blocks were tested. The results are as follows: Figure 3 , Figure 4 Examples 1 and 4 correspond to the results of carbon nanotube loading and graphene loading in the figure, and Examples 2 and 5 correspond to the results of graphene loading and carbon nanotube loading in the figure.
[0043] This application uses carbonate materials from a wide range of sources through low-energy rapid calcination technology to make the surface of the carbonate materials porous / roughened, which is more conducive to the loading of nanofunctional materials. The loading degree of the nanofunctional materials and modified carbonate materials is further enhanced through heat treatment. This solution is suitable for large-scale production, low cost, and the resulting material has good conductivity and mechanical properties, and is suitable for various construction fields.
[0044] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A multifunctional nano-loaded porous micro-aggregate, characterized in that: The invention comprises modified carbonate particles and nanometer functional materials loaded on the modified carbonate particles; the modified carbonate particles are obtained by roughening and / or making porous carbonate matrix materials.
2. The multifunctional nano-loaded porous micro-aggregate according to claim 1, characterized in that: The carbonate matrix material comprises limestone and / or dolomite.
3. The multifunctional nano-loaded porous micro-aggregate according to claim 1, characterized in that: The nano functional material includes one or more of graphene, carbon nanotubes and silver nanoparticles.
4. The multifunctional nano-loaded porous micro-aggregate according to claim 1, characterized in that: The particle size of the nano functional material is 10-20 nm.
5. The multifunctional nano-loaded porous micro-aggregate according to claim 1, characterized in that: The particle size of the carbonate matrix material is 20-50 μm.
6. The method for preparing the multifunctional nano-loaded porous micro-aggregate according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. calcining the carbonate matrix material to obtain modified carbonate particles; S2. Using an impregnation method, the nano-functional material is loaded on the modified carbonate particles to obtain a porous micro-aggregate precursor; S3. Heat-treating the porous micro-aggregate precursor to obtain the multifunctional nano-loaded porous micro-aggregate.
7. The method for preparing the multifunctional nano-loaded porous micro-aggregate according to claim 6, characterized in that: In step S1, the calcination temperature is 600-900°C, and the calcination time is 2-4h.
8. The method for preparing the multifunctional nano-loaded porous micro-aggregate according to claim 6, characterized in that: In step S2, the mass ratio of the nano-functional material to the carbonate matrix material is 5-8:
100.
9. The method for preparing the multifunctional nano-loaded porous micro-aggregate according to claim 6, characterized in that: In step S3, the heat treatment temperature is 100-200°C, and the heat treatment time is 1-3h.
10. Use of the multifunctional nano-loaded porous micro-aggregate obtained by the preparation method according to any one of claims 6 to 9 in building materials.
Citation Information
Patent Citations
Preparation method of antistatic material additive
CN102477232A
Preparation method of palladium or platinum and heteropolyacid co-loaded nano porous carbon composite material
CN112169841A
Conductive cement-based composite material based on loaded conductive phase fibers and preparation method of conductive cement-based composite material
CN117383855A
dry matter composition for concrete or mortar, containing porous grains
FI20096294A0
Porous calcium carbonate compound and production thereof
JP1995223813A